Andragogical Curriculum Orientation, Self-Regulated Learning, and Career Readiness in Nonformal Vocational Training - Rofik Jalal Rosyanafi; Yatim Riyanto; I Ketut Atmaja Johny Artha; Widodo Widodo; Heryanto Susilo; Wiwin Yulianingsih; Edwin Jaimes Villaflor (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Nonformal vocational training is increasingly required to prepare learners not only with technical competence but also with career readiness. However, limited empirical evidence explains how adult-oriented curriculum practices and learners’ self-regulation contribute to career readiness in nonformal vocational training institutions. This study aimed to examine the association between andragogical curriculum orientation, self-regulated learning, and career readiness among learners at LKP Lussy Surabaya. A quantitative ex post facto correlational design was applied using questionnaire data from 65 valid learners. Andragogical curriculum orientation was measured through self-concept, experience, readiness to learn, learning orientation, and learning motivation; self-regulated learning was measured through forethought, performance, and self-reflection; and career readiness was measured through concern, control, curiosity, and confidence. The results showed that andragogical curriculum orientation and self-regulated learning were positively and significantly associated with career readiness, with self-regulated learning emerging as the stronger predictor. Simultaneously, both variables explained 70.7% of the variance in career readiness. These findings indicate that career readiness in nonformal vocational training is shaped by adult-oriented learning experiences and learners’ regulatory capacity. This study provides an empirical basis for rethinking curriculum orientation beyond technical skill delivery toward stronger support for career readiness.